The Effect of Digitization of Personnel Services in Moderating the Influence of Employee Competence and Organizational Support on Performance at Regional Office VII BKN - Riki Herlangga Utama; Msy. Mikial; Ima Andriyani; Sari Sakarina (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study investigates the effect of digitization of personnel services in moderating the relationship between employee competence, organizational support, and employee performance at the Regional Office VII of the State Civil Service Agency (BKN) Palembang. The research emphasizes the strategic role of digital personnel systems in strengthening the contribution of human resource factors to performance outcomes within public sector organizations. This study employed a quantitative survey design involving 73 civil servants at the Regional Office VII of BKN Palembang. Data were analyzed using PLS-SEM with SmartPLS 4.0, and all measurement instruments met the required validity and reliability criteria (AVE > 0.50; CR > 0.70). The results show that employee competence and organizational support have significant positive effects on employee performance. The digitization of personnel services further enhances performance by improving efficiency and transparency, while partially moderating the effects of competence and organizational support on performance. The study concludes that personnel digitalization strengthens the impact of employee competence and organizational support on performance, indicating the need for an integrated strategy that combines competency development, organizational support, and effective digital personnel systems in public sector organizations. This research is limited by its focus on a single government institution, which may restrict the generalizability of the findings. In addition, the use of self-reported data may introduce response bias, and the cross-sectional design does not capture changes over time. This study contributes to human resource management and public administration literature by empirically confirming the moderating role of personnel digitalization in government settings, while offering practical insights for improving civil servant performance through integrated competence development, organizational support, and digital transformation.